Multilevel mixed methods research and educational psychology. Issue 4 (1st October 2020) - McCrudden, Matthew T.; Marchand, Gwen
Abstract: We discuss possible uses of multilevel mixed methods (M 3 ) research in educational psychology. To begin, we describe M 3 research and how such research can enable researchers to investigate potential variation at the group level and at the subgroup/individual level. We discuss why M 3 research designs are well-suited to investigate contextualized, nested phenomenon in education. Then, we describe the five purposes for conducting mixed methods research and provide examples of how M 3 designs can address these purposes. Next, we discuss our inquiry worldviews and how they inform our research. We describe three key assumptions (ontological realism, epistemic pluralism, and methodological eclecticism) and provide an example to illustrate how these assumptions can shape one's research. Finally, we discuss how M 3 research can be used to address equity and share several lessons we have learned as researchers who use mixed methods research.